2020
DOI: 10.3389/fmicb.2020.01074
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles at Biocompatible Dosage Synergistically Increases Bacterial Susceptibility to Antibiotics

Abstract: Antibiotics used to treat bacterial infections can become ineffective over time or result in the emergence of antibiotic resistant pathogens. With the advent of nanotechnology, silver nanoparticles (AgNPs) have gained significant attention as a therapeutic agent due to the well-known antimicrobial properties of silver. However, there are concerns and limited literature on the potential cytotoxicity of nanoparticles at effective antimicrobial concentrations. AgNPs prepared from silver nitrate with glucose reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 63 publications
(95 reference statements)
4
38
0
Order By: Relevance
“…AgNPs possess lower antibacterial concentration than those of LL-37 because AgNPs act as a nonspecific multimodal mechanism of action both insight and outsight of the bacterial cells. Thus, this advantage allows their effective antibacterial action at very low concentrations [ 44 , 45 ]. On the other hand, LL-37 is a cationic peptide, and the biological function of this peptide has been debated in several studies [ 3 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…AgNPs possess lower antibacterial concentration than those of LL-37 because AgNPs act as a nonspecific multimodal mechanism of action both insight and outsight of the bacterial cells. Thus, this advantage allows their effective antibacterial action at very low concentrations [ 44 , 45 ]. On the other hand, LL-37 is a cationic peptide, and the biological function of this peptide has been debated in several studies [ 3 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the interdisciplinary role AgNP has in modern medicine, recent reviews have discussed the possible environmental and economic impacts of AgNPs that are synthesized either naturally (green synthesis) or chemically [ 55 , 56 , 57 , 58 ]. Moreover, development of AgNPs using the biological method of synthesis with the use of bacteria, fungi and plant extracts [ 55 , 56 ] have shown to be ecofriendlier, cost effective and energy efficient [ 59 ], with reports of greater antimicrobial activity against pathogenic bacteria [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…By electrostatically interacting with cell membranes and binding to thiol groups of proteins, AgNPs are able to disrupt cell walls and metabolic processes, inactivate bacterial enzymes, increase cell permeability and generate reactive oxygen species. 7 , 32 More recently, it has been shown that AgNPs could not only improve the antifungal effects of antifungal agents, but also enhance antibacterial effects of antibiotics against a range of bacteria, including antibiotic resistant strains. 33 , 34 The synergistic and multimode antibacterial actions substantially decrease the need for high doses of antibiotics, therefore minimizing the potential of antibiotic resistance and toxicity to the neighbouring tissues.…”
Section: Irrigation Strategiesmentioning
confidence: 99%
“…58 , 59 This includes, but is not limited to, the average diameter, zeta potential, surface plasmon resonance peak and concentration. 32 , 35 , 36 , 57 A full list of the key physicochemical properties of nanomaterials can be found in Table 1 . 59 For example, Abbaszadegan et al provided a comprehensive characterization of the synthesized AgNPs with negative, neutral and positive surface charges, reporting the plasmon resonance peak was 400 nm, 425 nm and 407 nm, average size was 7.5 nm, 10.1 nm and 9.0 nm, concentration was 9.7 x 10 −8 mol L −1 , 4.0 x 10 −8 mol L −1 and 5.7 x 10 −8 mol L −1 and zeta potential was −38.0 mV, 0.0 mV and +50.0 mV respectively.…”
Section: Irrigation Strategiesmentioning
confidence: 99%